Geochemical characteristics of natural gases related to Late Paleozoic coal measures in China. (September 2018) - Gong, Deyu; Li, Jianzhong; Ablimit, Imin; He, Wenjun; Lu, Shan; Liu, Deguang; Fang, Chenchen
Abstract: By 2013, more than 20 gas fields related to Late Paleozoic coal measures have been discovered in China, primarily distributed in the Bohai Bay, Ordos, Sichuan, and Junggar Basins. The total proven reserve in these gas fields is more than 3200 × 10 9  m 3, accounting for 30.1% of the proven gas reserves in China. After analyzing the molecular compositions, stable carbon isotopes, and helium isotopes of 375 gas samples, genetic types and origins of the natural gas, as well as the secondary alterations it experienced, are discussed in this study. Most of the natural gas related to the Late Paleozoic coal measures are coal-type gas, with some of the gases from the Sichuan Basin and the Jingbian gas field in the Ordos Basin being oil-type gases generated from marine mudstones in the Permian Longtan Formation and marine carbonates in the Ordovician Majiagou Formation, respectively. The equivalent vitrinite reflectance values based on stable carbon isotopes of natural gases vary from 0.8% to 2.5%, indicating the mature to over mature stage. Positive carbon isotope series (δ 13 C-CH4  < δ 13 C-C2 H6  < δ 13 C-C3 H8 ) are observed in most gas samples, and carbon isotope reversals occur in the forms of δ 13 C-CH4  > δ 13 C-C2 H6 and δ 13 C-CH4  < δ 13 C-C2 H6  > δ 13 C-C3 H8 . The form of δ 13 C-CH4  > δ 13 C-C2 H6 is primarily resulted from the mixing of oil-type gases of different maturities, while the form of δ 13 C-CH4  < δ 13 C-C2 H6  > δ 13 C-C3 H8 is primarily resulted from the mixing of coal-type gases of different maturities. High concentrations of hydrogen sulfide in natural gas from the Sichuan Basin and the Chenghai gas field in the Bohai Bay Basin are resulted from thermochemical sulfate reduction (TSR), which causes, to some extent, the fractionation of carbon isotopes. By contrast, the fractionation of methane carbon isotopes resulting from the TSR effect is not clear. Carbon dioxide from the Bohai Bay and Junggar Basins is primarily biogenic, generated via the thermal decomposition of organic matter, while that from the Ordos Basin, Sichuan Basin, and Chenghai gas field is generated via the thermal decomposition of carbonates. Carbon dioxide related to the TSR effect has also contributed to the Sichuan Basin and Chenghai gas field. Highlights: Oil-type gas made contribution in the Jingbian gas field and Sichuan Basin. δ 13 C reversal is caused by admixture of gas with different maturities or origins. TSR resulted in the high concentration of H2 S and δ 13 C-C2 H6 fractionation. CO2 is primarily biogenic or carbonate-derived.